Fostering students’ willingness to act pro-environmentally through an identity-oriented socio-scientific exhibition on the energy transition - Kellberg, Sarah; Nordine, Jeffrey; Keller, Melanie; Lewalter, Doris (Frontiers in Education, 2023)
Successfully communicating the importance of a global energy transition toward carbon-free energy sources and increasing participation in it depends on society as a whole, including the socio-cultural identities and personal values of all involved. Since a person's willingness to engage in the energy transition is strongly influenced by his or her social environmental identity, we argue that interventions offering students opportunities to develop this part of themselves should foster their overall willingness to do so. We argue that modern museum exhibitions on socio-scientific issues addressing visitors as individual, social or political actors, represent particularly suitable sites for such an approach. We investigated the extent to which students’ overall willingness to act pro-environmentally changed after visiting a socio-scientific exhibition on the energy transition and the extent to which students’ subsequent overall willingness to act was influenced by their prior conceptual knowledge about energy and topic-related interest. Data for the study was collected in a pre-post design, with students (N = 185) visiting the exhibition for 90 minutes in between. We found that students’ overall willingness to act changed significantly from prior to after their exhibition visit, and we found that students’ prior energy knowledge but not their interest impacted their willingness to act after the visit to the exhibition. Based on these findings, we discuss that providing a broad range of opportunities for identity work to students outside of the school context fosters their willingness to act on a global scale – and that modern socio-scientific museum exhibitions are thus a useful way to complement formal education.